The Quality of life assessment in patients treated due to chronic pancreatitis - Dragović, Saša; Vulović, Maja; Stamenković, Dušica; Rančić, Nemanja; Mitrović, Miroslav; Bezmarević, Mihailo; Jovanović, Milan; Pantić, Ivan; Rujanovski, Zoran; Lepić, Sanja; Milev, Boško (Vojnosanitetski pregled, 2022)
Background/Aim. Chronic pancreatitis (CP) causes inflammatory changes in the tissue of the pancreas, resulting in irreversible tissue damage. Pain, endocrine, and exocrine pancreatic insufficiency develop, thereby reducing the quality of life (QoL)  of patients. The aim of the study was to determine the significance of surgical treatment in improving the QoL of patients with CP. Methods. QoL assessment of 50 patients diagnosed with CP was performed using a certified Euro Quality of Life-5 Dimension-5 Level (EuroQol-5D-5L) Questionnaire translated into Serbian. According to the method of treatment, patients completed the questionnaire. Patients were divided into two groups (conservatively treated – CT and surgically treated – ST), and all comparisons were made between groups. Results. Patients in stage B of CP were divided into two groups of 25 patients. The mean age in the ST group was 48.56 ± 11.91, and in the CT group was 51.08 ± 11.61 (p = 0.452). The male/female ratio in the ST group was 18/7, and in the CT group was 22/3 (p = 0.289). Pain in the ST group was present in 23 patients, and in the CT group was present in 18 patients (p = 0.141). Loss of appetite in the ST group was present in 7 patients and in the CT group in 10 patients (p = 0.256). Weight loss in both groups was equal (p = 1.000). Based on the EuroQol-5D-5L Questionnaire, significant differences were found (p
Keywords: drug therapy; pancreatitis, chronic; quality of life; surgical procedures, operative; surveys and questionnaires